Hexavalent Chromium Reduction of Artificial Waste Using Resin Immobilized Photocatalyst TiO2 - Moch. Andy Wibisono; Euis Nurul Hidayah; Baranitharan Ethiraj; Reffany Choiru Rizkiarna (Universitas PGRI Madiun, 2025)
Photocatalysis is a process that can be used to reduce hexavalent chromium in wastewater. Therefore, this study aimed to analyze the effect of a semiconductor in the form of Resin Immobilized Photocatalyst (RIP)-TiO2 on the reduction of Cr (VI), as well as the effect of pH and catalyst mass. In the process, RIP-TiO2 was produced using rutile crystal TiO2 and cation resin. The study was conducted in a column bed with continuous flow and UV lamp irradiation. Sampling was performed every 5, 15, 45, and 60 minutes, as well as the use of 30 and 40 g of RIP-TiO2. The statistical results from a Two-Way Analysis of Variance (ANOVA) showed no significant differences in pH variation and catalyst mass. However, the best operating conditions were obtained at pH 5 and a catalyst mass of 40 g with a removal rate of 21.32%. These results suggested that pH adjustment had no significant effect on the reduction of Cr(VI) to Cr(III) using RIP-TiO₂ catalyst in the photocatalytic process. Further studies are needed to evaluate other factors, such as UV light intensity, contact time, and physical characteristics of the catalyst, capable of improving the efficiency of the RIP-TiO₂ system.